Study of Bridge Demolition DOT Survey and Available Standard Specifications - Nazanin Rezaei; David Garber (Advances in Civil Engineering)
There are many damaged bridges in the United States which are either structurally deficient or functionally obsolete and require replacement or rehabilitation, many using accelerated bridge construction (ABC) techniques. Before a bridge is replaced or rehabilitated, the old structure or component needs to first be demolished. Although the AASHTO LRFD Bridge Design Specification presents minimum bridge design requirements, there is limited information about bridge demolition available for designers and contractors in this field. More study is required to determine best practices in demolition administration and avoid further unintentional events. This study presents the results from a survey prepared and disseminated through a research effort under the Accelerated Bridge Construction University Transportation Center (ABC-UTC). This survey was sent out to all State Departments of Transportation (DOTs). The results of the survey reveal the need for additional guidance in bridge demolition administrations at a national level. According to the results of this study, contractors are the most important part of bridge demolition projects from injuries, fatalities, and responsibility point of view.